2007
DOI: 10.1007/s00213-007-1022-6
|View full text |Cite
|
Sign up to set email alerts
|

Does context influence the duration of locomotor sensitization to ethanol in female DBA/2J mice?

Abstract: Rationale-Repeated exposure to many abused drugs produces a progressive increase in locomotor sensitivity, referred to as locomotor sensitization. Locomotor sensitization may persist for some time following termination of repeated drug administration, and contextual learning appears to facilitate expression of the behavioral phenomenon. However, relatively little is known about the persistence of and the degree to which contextual learning influences locomotor sensitization to alcohol (ethanol).Objectives-The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…This conclusion is supported by the results of the test session, both when ethanol sensitization is recorded on the whole 30-min test session and when only the first 5 min of the test session are considered. These results are in agreement with those of Boehm et al (2008) who found no significant differences in the first sensitization test between DBA/2J mice sensitized within or outside the test context. The present results also agree with those of several other authors who routinely use sensitization procedures in which ethanol is injected in the colony room (e.g., Meyer and Phillips 2007;Quadros et al 2002).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This conclusion is supported by the results of the test session, both when ethanol sensitization is recorded on the whole 30-min test session and when only the first 5 min of the test session are considered. These results are in agreement with those of Boehm et al (2008) who found no significant differences in the first sensitization test between DBA/2J mice sensitized within or outside the test context. The present results also agree with those of several other authors who routinely use sensitization procedures in which ethanol is injected in the colony room (e.g., Meyer and Phillips 2007;Quadros et al 2002).…”
Section: Discussionsupporting
confidence: 95%
“…Such an experimental protocol has been used to demonstrate the context dependency of the behavioral sensitization to many drugs, including cocaine, amphetamines, dopamine agonists, and nicotine (Crombag et al 2000;Hooks et al 1993;Reid et al 1996;Szumlinski et al 1997). In contrast to these drugs, few experimental studies have yielded clear and unambiguous results on the context dependency of ethanol sensitization (Boehm et al 2008;Cunningham and Noble 1992;Meyer et al 2005;Quadros et al 2003). To examine if ethanol acts like psychostimulants to induce context-dependent sensitizing effects, we compared the effects of ethanol injected in a specific test or home cage environment.…”
Section: Introductionmentioning
confidence: 99%
“…On days 4-13 mice assigned to the RE group received a 2.5 g/kg ethanol dose once daily and mice in the RS group continued to receive an equivalent volume of saline each day. This 0.5 g/kg higher dose was chosen based on literature demonstrating its effectiveness at inducing strong locomotor sensitization in mice using similar paradigms (Lessov & Phillips, 1998; Meyer et al , 2005), including data from our lab (Boehm et al, 2008). None of the mice were tested in the locomotor activity testing chambers following injection on days 4-13; mice were placed immediately into their home cage following injection.…”
Section: Methodsmentioning
confidence: 99%
“…We used female DBA/2J mice as described in other studies (Boehm et al, 2008;Botia et al, 2012;Didone et al, 2008). Mice were purchased from Janvier (Le Genest Saint Isle, France) and were housed 10 per cage and acclimated to the colony room for at least 10 days.…”
Section: Subjectsmentioning
confidence: 99%